Efektivitas Penggunaan Pestisida Organik Dalam Mengendalikan Hama Pada Tanaman Sayuran - Ricardo Fondraradodo Harefa (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This study aims to test the effectiveness of using organic pesticides in controlling pests on vegetable crops. The use of organic pesticides is increasingly popular as an environmentally friendly alternative compared to synthetic pesticides, which can damage ecosystems. In this study, the organic pesticides tested were derived from natural materials such as plant extracts and microorganisms. The research was conducted on agricultural land planted with various types of vegetables, such as tomatoes, mustard greens, and eggplants. The results showed that organic pesticides significantly reduced pest populations without decreasing crop yields. Additionally, the use of organic pesticides did not have a negative impact on soil and water quality around the plants. Thus, the use of organic pesticides can be an effective and sustainable solution for pest control in vegetable crops.